The Role of the Pterional Approach in the Surgical Treatment of Olfactory Groove Meningiomas: A 20-year Experience - Bitter, Andrej D.; Stavrinou, Lampis C.; Ntoulias, Georgios; Petridis, Athanasios K.; Dukagjin, Morina; Scholz, Martin; Hassler, Werner (Journal of Neurological Surgery Part B: Skull Base, 2013)
Background Olfactory groove meningiomas remain surgically challenging. The common microsurgical approaches suffer from late exposure of the neurovascular structures. Conversely, the pterional approach has the advantage of early dissection of the posterior neurovascular complex.Methods We reviewed the records of patients treated for olfactory groove meningioma in our department between 1991 and 2010. A total of 61 patients underwent removal of olfactory groove meningiomas via the pterional approach. These included 58 primary and 3 recurrent tumors. Mean overall follow-up time was 122 months.Results Early exposure and dissection of the internal carotid artery, middle cerebral artery, anterior cerebral artery, and optic nerve was feasible in all cases. Complete tumor removal was achieved in 60 patients. Morbidity and mortality rates were 26% and 1.6% respectively. Postoperative complications included epileptic seizures (five patients) and cerebrospinal fluid (CSF) leak (two patients). During follow-up, we recorded three tumor recurrences.Conclusions The pterional approach appears to be an excellent solution for the treatment of olfactory groove meningiomas. Its foremost advantage is early visualization of the posterior neurovascular complex. Moreover, it allows frontal sinus preservation and timely tumor devascularization and avoids excessive brain retraction. The pterional view is familiar to most neurosurgeons and therefore the transition to this technique is fairly straightforward.
Keywords: pterional approach; olfactory groove meningiomas; surgical treatment; meningioma removal